2021
DOI: 10.1007/s10765-021-02911-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacities of l-Arginine, l-Aspartic Acid, l-Glutamic Acid, l-Glutamine, and l-Asparagine

Abstract: In an effort to establish reliable thermodynamic data for amino acids, heat capacity and phase behavior is reported for l-arginine (CAS RN: 74-79-3), l-aspartic acid (CAS RN: 56-84-8), l-glutamic acid (CAS RN: 56-86-0), l-glutamine (CAS RN: 56-85-9), and l-asparagine (CAS RN: 70-47-3). Prior to heat capacities measurement, thermogravimetric analysis was performed to determine decomposition temperatures. Crystal heat capacities of all five amino acids were measured by Tian-Calvet calorimetry in the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(41 reference statements)
2
3
0
Order By: Relevance
“…The deviations of temperature and enthalpy as well as the sensitivity of calorimetric and balance for the DSC/TGA instrument (Netzsch 200 f3, Germany) are ±0.1 K, 1%, 0.1 μW, and 0.1 μg, respectively. The DSC/TGA curves showed that the decomposition process of L -glutamine occurred at 450.03 K, as shown in Figure , which is consistent with the literature-reported results. , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The deviations of temperature and enthalpy as well as the sensitivity of calorimetric and balance for the DSC/TGA instrument (Netzsch 200 f3, Germany) are ±0.1 K, 1%, 0.1 μW, and 0.1 μg, respectively. The DSC/TGA curves showed that the decomposition process of L -glutamine occurred at 450.03 K, as shown in Figure , which is consistent with the literature-reported results. , …”
Section: Resultssupporting
confidence: 91%
“…The DSC/TGA curves showed that the decomposition process of L-glutamine occurred at 450.03 K, as shown in Figure 4, which is consistent with the literature-reported results. 26,27 4.3. Solubility Data.…”
Section: Pxrd Resultsmentioning
confidence: 99%
“…The considerable weight loss was only observed in the temperature range between 615 and 800° C and was 43-44%, which agrees with the theoretical loss of 44 wt%, attributed to the decomposition of CaCO3 into CaO and CO2 (Tanaka and Naka, 2010). TGA also rules out the presence of any arginine in CaCO3 particles since there is no drastic weight loss in the temperature range of 500-600° C, which is the degradation range of arginine (Pokorný et al, 2021). The absence of arginine in CaCO3 particles suggests that the formation mechanism, which involves the binding of amino acid molecules to primary nanoparticles (Fig.…”
Section: Optimization Of Ca 2+ Conversionsupporting
confidence: 85%
“…This work is a continuation of our project, for which the goal is to establish reliable thermodynamic data along the saturation curve for a group of proteinogenic amino acids [ 1 , 2 , 3 , 4 , 5 ]. The five amino acids studied in this work (L-cysteine, L-serine, L-threonine, L-lysine, L-methionine) are white crystalline compounds under ambient conditions and are reported to decompose at/prior to melting in the temperature range 523–573 K [ 6 ].…”
Section: Introductionmentioning
confidence: 99%